A national program to advance dementia research in Vietnam - Huyen Thi Thanh Vu; Tuan Anh Nguyen; Thu Thi Hoai Nguyen; Anh Trung Nguyen; Duyen Tran; Huong Nguyen; Ladson Hinton; Thang Pham (BMC, 2024)
Abstract Background As Vietnam and other low- and middle-income countries (LMIC) experience a rapid increase in the number of people living with dementia, an acute need exists to strengthen research capacity to inform policy, improve care and support, and develop national dementia plans. We describe the development and early outcomes of an National Institutes of Health (NIH)/National Institute on Aging (NIA)-funded national dementia research capacity building program in Vietnam. Methods The research capacity building program commenced in 2019 and has three components: (1) Vietnam Alzheimer's and other dementias research Network (VAN), (2) a mentored pilot grant program, and (3) research training, networking, and dissemination activities. The pilot grant program funds Vietnamese researchers for one to two years to conduct research focusing on Alzheimer's Disease and Alzheimer's Disease Related Dementias (AD/ADRD). Grants are reviewed and scored using NIH criteria, and priority is given to pilot grants with policy relevance and potential for future funding. An international pool of high-income country (e.g., United States, Australia, and United Kingdom) mentors has been engaged and mentors paired with each funded project. Training and networking activities include workshops on AD/ADRD research topics and regular meetings in conjunction with Vietnam's annual national dementia/geriatric conferences. Dissemination is facilitated through targeted outreach and the creation of a national network of institutions. Results Over four years (2019-2023), we received 62 applications, reviewed 58 applications, and funded 21 projects (4-5 per year). Funded investigators were from diverse disciplines and institutions across Vietnam with projects on a range of topics, including biomarkers, prevention, diagnosis, neuropsychological assessment, family caregiver support, dementia education, and clinical trials. A network of 12 leading academic and research institutions nationwide has been created to facilitate dissemination. Six research training workshops have been organized and included presentations from international speakers. Grantees have published or presented their studies at both national and international levels. The mentoring program has helped grantees to build their research skills and expand their research network. Conclusion This research capacity building program is the first of its kind in Vietnam and may serve as a useful model for other LMIC.